Обратная задача анизотропийного анализа робастного качества дискретных линейных стационарных систем - Курдюков, А. П.; Тимин, В. Н.; Чайковский, М. М. (Видавництво Львівської політехніки, 2011)
This paper addresses the inverse problem of anisotropy-based performance analysis of linear discrete timeinvariant system. The inverse problem consists in finding the maximum level of mean anisotropy of random input sequence corresponding to some given value of anisotropic norm of system.A unique solution is determined by solving a system of four cross-coupled nonlinear algebraic equations including Riccati,Lyapunov, and two scalar equations with respect to traces of symmetric matrices.
Keywords: линейные системы; случайные возмущения; норма; анизотропия